Beyond ergosterol: Strategies for combatting antifungal resistance in Aspergillus fumigatus and Candida auris. (3rd March 2023) - Cruz, Ricardo; Wuest, William M.
Abstract: Aspergillus fumigatus and Candida auris are historically problematic fungal pathogens responsible for systemic infections and high mortality rates, especially in immunocompromised populations. The three antifungal classes that comprise our present day armamentarium have facilitated efficacious treatment of these fungal infections in past decades, but their potency has steadily declined over the years as resistance to these compounds has accumulated. Importantly, pan-resistant strains of Candida auris have been observed in clinical settings, leaving affected patients with no treatment options and a death sentence. Many compounds in the ongoing antifungal drug discovery pipeline, similar to those within our aforementioned trinity, are predicated on the binding or inhibition of ergosterol. Recurring accounts of resistance to antifungals targeting this pathway suggest optimization of ergosterol-dependent antifungals is likely not the best solution for the long-term. This review aims to present several natural products with novel or underexplored biological targets, as well as similarly underutilized drug discovery strategies to inspire future biological investigations and medicinal chemistry campaigns.